Amplification of dissipative solitons with a polarisation-maintaining tapered fibre amplifier. (December 2018) - Kuznetsov, A.G.; Kharenko, D.S.; Babin, S.A.
Abstract: The generation of strongly chirped dissipative solitons offers great opportunities for generating high-power laser pulses of short duration. We demonstrate the possibility of amplifying such pulses in a polarisation-maintaining tapered fibre having 32 μm mode diameter at the output end. Highly chirped pulses with a repetition rate of 14.3 MHz and a duration of 10 ps at 1055 nm centre wavelength are amplified in an all-fibre circuit to 2.11 μJ energy and compressed by diffraction gratings to a duration of ∼297 fs. Reducing the pulse repetition rate to 1 MHz allows a 16.5 μJ output pulse energy to be achieved without manifestations of SRS and self-phase modulation in the spectrum.